Local History Collection in Public Libraries of South 24 Parganas: A Study - Moitra, Sudeshna; Dutta, Chaitali (Journal of Information and Knowledge, 2019)
Public library has the social responsibility to meet the local community requirements for knowledge, information, education, culture, recreation, and so on. The responsibility includes preserving local history materials of a particular locality. This paper reflects the present scenario of collection, preservation, dissemination, use pattern of local history materials and user demand for such collection in the Government-sponsored public libraries (District Library, Sub-divisional Libraries and Town Libraries) in South 24 Parganas district in West Bengal. Every library was visited personally to interview the Librarian/In-charge and data were collected through a structured questionnaire. Library users were also interviewed through a separately structured questionnaire by applying random sampling method. Collected data were analysed to find out the present situation and issues related to building local history collection and rendering effective associated services. Findings reflect the major hindrances responsible for the state of sources of local history in the South 24 Parganas. Some recommendations have been made.